Residual stress of high strength steel box T-joints Part 2 : numerical study - Chiew, Sing Ping (2014)
In Part 2 of this study, 3D fully coupled thermal-stress analyses were conducted to simulate the welding process and predict the welding residual stress distributions of the high strength steel box section T-joints. The accuracy of the numerical model is validated by comparing the modeling results with the experimental results. After validating the accuracy of the numerical model, a small scale parametric study was carried out to investigate the influences of joint angle, the starting point of joint welding, the preheating temperature, the brace-to-chord width ratio and the welding speed on the magnitudes and distributions of residual stress along the chord weld toe of the joints.